Optimizing Pop Up Book Media for Students of Teacher Training and Education at Faculty of Teacher Training and Education FKIP UNTAN - Maha Lastasabuju Basafpipana Habaridota (International Journal of Science and Applied Science: Conference Series, 2021)
Educators individually or jointly develop and improve the quality of their profession. This is part of the code of ethics that must be developed for all educators because of the great influence of educators on the results of their education. The design used is qualitative. Based on the expert's opinion, it can be concluded that descriptive research is research that presents everything based on the collected facts, whether it is an activity, event, symptom systematically and as it is. There are three main problems formulated in this study, namely how to prepare materials and tools, design and produce Pop-Up Book media for students majoring in basic education, Faculty of Teacher Training and Education FKIP UNTAN. Optimizing the preparation of materials and tools for designing Pop-Up Book media for students of Faculty of Teacher Training and Education, it means that the ability of students to prepare the materials and tools needed is 4.87 with a good category. The results of the Pop-Up Book media design for students majoring in Faculty of Teacher Training and Education, FKIP UNTAN. It is interpreted as the ability to produce products as well as being able to present 4.75 media with good category.